INDUCTIVE PROPERTIES OF BENT VORTEX CORDS AND THEIR APPLICATION TO CONSTRUCTING A MODEL OF WAKE VORTEX HELICOPTER ROTOR - V. I. Shaydakov (Научный вестник МГТУ ГА, 2016)
This article provides information about the properties of BENT inductive vortices capable of under the influence of self-induction to move at a speed independent of circulating Г, the size of the nucleus and the local curvature of the individual sections of vortex tube. For numerical calculations the method of accounting for the self-induction at the nodal point of the vortex tube segments. Formulas and recommendations for the construction of models the free-vortex wake in the rotor blade theorie